Correction to: The LUTADOSE trial: tumour dosimetry after the first administration predicts progression free survival in gastro‑entero‑pancreatic neuroendocrine tumours (GEP NETs) patients treated with [177Lu] Lu‑DOTATATE. - Maccauro, Marco; Cuomo, Mariarosaria; Bauckneht, Matteo; Bagnalasta, Matteo; Mazzaglia, Stefania; Scalorbi, Federica; Argiroffi, Giovanni; Kirienko, Margarita; Lorenzoni, Alice; Aliberti, Gianluca; Pusceddu, Sara; Giuseppina, Calareso; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
The article addresses a correction regarding the name of Dr. Enrico Matteo Garanzini, which was inaccurately presented in a previously published article. The correction clarifies that his name should be listed as Garanzini Enrico Matteo. This erratum serves to ensure the accuracy of authorship in the academic record. The publisher, Springer Nature, maintains a neutral stance on jurisdictional claims related to published maps and institutional affiliations.